(untitled) (Philologia, 2024)
The aim of this paper is to analyze the reception of Elsa Triolet’s novels in the French weekly Les Lettres françaises. We analyze and examine the critical texts and interviews of the author regarding her novel Le Monument (1957), followed by the texts referring to her novel cycle L’Âge de nylon: Roses à crédit (1959), Luna-Park (1959), L’Âme (1962). First, we focus on the articles on the novel Les Manigances (1961), published outside this cycle, continuing with the articles on the two novels that belong to the same cycle, Le Grand-Jamais (1965) and Écoutez-voir (1968). Our research shows a keen interest of Les Lettres françaises in Elsa Triolet’s novels. Literary critics of the time saw great potential, diversity and richness of themes in Triolet’s texts. From the analyzed texts, we observed that this writer’s novels were positively received, with critics utilizing a variety of techniques to introduce the author’s oeuvre to a wider audience.